Impact of Organic Farming on Agronomic Crops Productivity, Grain Quality and Antioxidant Activity - Amit Kesarwani; Sweta Shikta Mahapatra; Shih Shiung Chen (New Ideas Concerning Science and Technology Vol. 4, 2021)
The aim of the study is to understand the mechanism of chemical or organic fertilizer influence on physicochemical, starch pasting properties and antioxidant characteristics of rice grain. Similarly, how some of the indigenous liquid organic manure brings the production changes in the finger millet crop. For rice, the study was conducted for 2 years in popular Japonica cultivars i.e., Kaohsiung No. 139 and Taikeng No.16 which grown twice a year in Taiwan. The results highlighted that physicochemical properties were least effected by external factors and found genetically inherited. Major pasting properties such as Peak viscosity, Setback value and pasting temperature improved under organic farming, however in further analysis eating and cooking quality reported no significant changes except aroma in rice. Interestingly, the organically grown rice has proven to be better in higher accumulation of secondary metabolites (2,2-diphenyl-1-picrylhydrazyl (DPPH), flavonoid content, and ferrous chelating capacity). In nutshell, organic had role in changing some metabolic conditions in crop but genetic traits and environment have significant effect with least variation under agronomic practices in rice. The role of chemical fertilizer was strong in finger millet performance compared to other organic sources.